Selective GaN sublimation and local area regrowth for co-integration of enhancement mode and depletion mode Al(Ga)N/GaN high electron mobility transistors. (7th December 2020) - Thi Huong, Ngo; Comyn, Rémi; Chenot, Sébastien; Brault, Julien; Damilano, Benjamin; Vézian, Stéphane; Frayssinet, Eric; Cozette, Flavien; Rodriguez, Christophe; Defrance, Nicolas; Lecourt, François; Labat, Nathalie; et al.
Abstract: In this paper, we report on the fabrication of a normally-off Al(Ga)N/GaN high electron mobility transistor with selective area sublimation under vacuum of the p type doped GaN cap layer. This soft method makes it possible to avoid damages otherwise induced by post processing with reactive ion etching techniques. The GaN evaporation selectivity is demonstrated on AlN as well as on AlGaN barrier layers. Furthermore, by properly choosing the AlGaN barrier thickness and composition it is possible to co-integrate a normally-off with a normally-on device on the same substrate. Finally, a local area regrowth of AlGaN can complement this process to increase the maximum drain current in the transistors.